Statement by the Managing Director on Updating the Strategic Directions in the Medium-Term Budget : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2011)
In early 2008, the Fund launched ambitious reforms to enhance its ability to deliver the economic and financial analysis, member support, and multilateral collaboration essential to promote global stability. The reform agenda called for: (i) stronger surveillance through sharpened multilateral and regional tools, analysis of macro-financial and international linkages, and greater use of cross-country work in bilateral surveillance; (ii) sharper policy advice for low-income countries, with emphasis on areas of core Fund expertise; (iii) improved capacity building efforts to be augmented by more external fund-raising; and (iv) a modernized governance structure to enhance the Fund's legitimacy and better reflect its role as a universal institution capable of facilitating global cooperation and action. With the onset of the global financial crisis later in 2008, the Fund also committed to reforming its lending toolkit, including overhauling its concessional support instruments, to ensure that its facilities fully met members' evolving needs.